Investigating Consumers’ Motives for Attending Major Cultural Events - Muresherwa, Gift (Acta Universitatis Danubius. Œconomica, 2025)
Cultural events are increasingly recognised as drivers of tourism, social cohesion, and local economic activity. However, limited empirical research exists, especially on the motivations influencing attendance, particularly in African contexts. This study, therefore, explores consumers’ motives for attending major cultural events in South Africa, focusing on the Cape Town Carnival (CTC) event. The study followed a quantitative research design, using survey data collected from attendees during the 2023 and 2024 editions of the event. Data were analysed using IBM SPSS software to identify the key reasons for attending this annual event. Findings reveal that attendees were primarily motivated by the pursuit of fun and entertainment, the influence of family and friends, and the convenience of the event’s location. Cultural appreciation and loyalty among repeat attendees also emerged as significant themes, while other factors such as the outdoor atmosphere and spontaneous participation were less common. These insights highlight the multifaceted nature of consumer behaviour at cultural events. The study recommends that organisers focus on enhancing the experiential and cultural value of the carnival event. It also highlights the importance of leveraging social networks and accessibility to help broaden participation. Overall, the findings provide valuable guidance for event marketing and destination branding in Cape Town.